Crystallographic and mutational analyses of cystathionine β‐synthase in the H2S‐synthetic gene cluster in Lactobacillus plantarum. (10th February 2017) - Matoba, Yasuyuki; Yoshida, Tomoki; Izuhara‐Kihara, Hisae; Noda, Masafumi; Sugiyama, Masanori
Abstract: Cystathionine β‐synthase (CBS) catalyzes the formation ofl ‐cystathionine froml ‐serine andl ‐homocysteine. The resultingl ‐cystathionine is decomposed intol ‐cysteine, ammonia, and α‐ketobutylic acid by cystathionine γ‐lyase (CGL). This reverse transsulfuration pathway, which is catalyzed by both enzymes, mainly occurs in eukaryotic cells. The eukaryotic CBS and CGL have recently been recognized as major physiological enzymes for the generation of hydrogen sulfide (H2 S). In some bacteria, including the plant‐derived lactic acid bacterium Lactobacillus plantarum, the CBS‐ and CGL‐encoding genes form a cluster in their genomes. Inactivation of these enzymes has been reported to suppress H2 S production in bacteria; interestingly, it has been shown that H2 S suppression increases their susceptibility to various antibiotics. In the present study, we characterized the enzymatic properties of the L. plantarum CBS, whose amino acid sequence displays a similarity with those of O ‐acetyl‐l ‐serine sulfhydrylase (OASS) that catalyzes the generation ofl ‐cysteine from O ‐acetyl‐l ‐serine (l ‐OAS) and H2 S. The L. plantarum CBS showsl ‐OAS‐ andl ‐cysteine‐dependent CBS activities together with OASS activity. Especially, it catalyzes the formation of H2 S in the presence ofl ‐cysteine andl ‐homocysteine, together with the formation ofl ‐cystathionine. The high affinity towardl ‐cysteine as a first substrate and tendency to usel ‐homocysteine as a second substrate might be associated with its enzymatic ability to generate H2 S. Crystallographic and mutational analyses of CBS indicate that the Ala70 and Glu223 residues at the substrate binding pocket are important for the H2 S‐generating activity. Abstract : PDB Code(s):5B1H ;5B1I